To determine which equation is equivalent to \(4x + 6 = 1\), we will transform each option and check if it simplifies to \(4x + 6 = 1\).
- Starting Equation: \(4x + 6 = 1\)
Next, we will solve for \(x\) in this equation:
\[ 4x = 1 - 6 \ 4x = -5 \ x = -\frac{5}{4} \]
Now let's check each option:
Option A: \(1 + 3(x + 2) = 1\)
Distributing \(3\):
\[ 1 + 3x + 6 = 1 \ 3x + 7 = 1 \ 3x = 1 - 7 \ 3x = -6 \ x = -2 \]
Not equivalent.
Option B: \(5(x + 2) - x = 1\)
Distributing \(5\):
\[ 5x + 10 - x = 1 \ 4x + 10 = 1 \ 4x = 1 - 10 \ 4x = -9 \ x = -\frac{9}{4} \]
Not equivalent.
Option C: \(18 + 6(x - 2) - 2x = 1\)
Distributing \(6\):
\[ 18 + 6x - 12 - 2x = 1 \ 4x + 6 = 1 \]
This is equivalent!
Option D: \(9x - 5(x - 1) - 1 = 1\)
Distributing \(-5\):
\[ 9x - 5x + 5 - 1 = 1 \ 4x + 4 = 1 \ 4x = 1 - 4 \ 4x = -3 \ x = -\frac{3}{4} \]
Not equivalent.
The only option that simplifies to \(4x + 6 = 1\) is:
C. \(18 + 6(x - 2) - 2x = 1\)